Evaluación interactiva en el área de ciencias naturales para el séptimo año de la educación general básica, año 2014 - Pico Salinas, Bertha Fabiola (2015)
This research allowed us to have a teaching resource for students’ learning contributing significantly to change traditional evaluations without reducing important and useful generating a resource for interactive assessments. For which was designed a descriptive study with field mode to collect the necessary information using the interview technique for managers and the survey of teachers and students of the institution. Through research was determined that a high percentage of teachers in the school don’t use any type of interactive material to evaluate the students aspect fundamentally limited by poor training and limited availability of tools for interactive evaluation in the teaching – learning process. For this reason, it is proposed as an alternative solution to the problem implementing an interactive CD of evaluation to improve teaching skills of teachers and the quality of student learning.